Vibrio Septicemia Diagnosed With Next-Generation Sequencing: A Case Report. Issue 4 (2nd December 2022) - Chen, Zutao; Liu, Xiao; Wang, Yajuan; Yao, Yunhai
Abstract: Vibrio vulnificus and Vibrio parahaemolyticus are marine gram-negative bacilli that can cause septicemia and gastrointestinal and wound infections. Early suspicion, diagnosis and appropriate antibiotic therapy for those infections are essential as delay can adversely affect the outcome. Here, we report a patient who developed a V. vulnificus and V. parahaemolyticus infection after contact with a fishing net. The cause of infection was finally diagnosed by metagenomic next-generation sequencing. The patient required an emergency amputation of the upper- and middle-third of the right upper limb.